Method for Nest Detection of the Yellow-Legged Hornet in High Density Areas - Rojas-Nossa, Sandra V.; Álvarez, Patricia; Garrido, Josefina; Calviño-Cancela, María (Frontiers in Insect Science, 2022)
The Asian hornet Vespa velutina is a social predator that has invaded several countries of Europe and Asia, impacting pollinators, apiculture and human health. One of the few effective control methods developed so far is the early destruction of nests. However, they are often build among dense vegetation, being difficult to detect. The aim of the method described here is to detect nests with a simple procedure, utilizing readily available materials, for widespread use in infested areas. The method has two phases, the first phase involves capturing and marking hornets lured by a protein bait and recording the flight courses of individuals to the nest and the time needed to complete a bait-nest-bait round trip, to estimate the distance. Collecting this information from two (or more) bait stations allows to delineate the approximate area of the nest. The second phase aims at the precise location of the nest, using sugary baits in the vicinity of the nest and conspicuous marks attached to the hornets captured, to visually follow them up to the nest. This method is an alternative to other methods that are either ineffective in areas with high nest density or require expensive equipment and specialized training.